KETIMPANGAN EKONOMI DAN KEBIJAKAN PEMERATAAN PEMBANGUNAN DI PROVINSI BANTEN - Nidya Waras Sayekti (Pusat Kajian Anggaran, 2017)
During 16 years of development since regional autonomy, economic inequality is still a problem in Banten Province. The imbalance of growth between the South and North Region sharpens the socio-economic welfare gap in Banten Province. The districts/municipalities in the Northern Territory have Gross Regional Domestic Income (GRDP) greater than districts / municipalities located in the Southern Region whereas the southern region has an area of more than 60 percent of the total area of Banten. This research used descriptive method with qualitative approach to give a thorough analysis about policy of economic gap equation and development in Banten Province. The gini ratio of Banten Province for the year 2012 - 2016 is the highest in 2014 (0.424) and tends to decrease to 0.392 in 2016. One of the efforts of the Banten Provincial Government is to implement a long-term development strategy by maximizing the potential of the remaining area, the southern part as the minapolitan area. To support this and to reduce economic imbalances, local governments need to increase inter-regional connectivity through improved land, air and sea transportation and the infrastructure linking new growth centers. Through this strategy is expected to suppress the economic imbalances that occur and even distribution of development felt more Banten community.